Perfil epidemiológico da infecção causada por Treponema pallidum em pacientes portadores do vírus da imunodeficiência humana (HIV) em Dourados – MS - Silva, Jhully Stéphani Santana Lima (2023)
The co-infection between human immunodeficiency virus (HIV) and syphilis, caused by the bacterium Treponema pallidum, is a frequently observed combination that can intensify the adverse impacts of both diseases, including clinical management and therapeutic challenges. Understanding the factors associated with the occurrence of this co-infection is of vital importance to support more effective screening and treatment strategies. This study aims to identify the occurrence and correlated factors of Treponema pallidum co-infection in HIV-positive patients in Dourados. Through a descriptive, cross-sectional, and observational approach, a standardized questionnaire was administered, and blood samples were collected for rapid treponemal tests in patients at the Specialized Care Service (SAE) in Dourados. Considering sociodemographic and behavioral characteristics, it was observed that out of the 57 participating patients, the majority (59.65%) were men aged between 50 and 69, of mixed ethnicity, homosexual orientation, and single marital status. Among the 57 interviewed patients, 47 tested positive for HIV, and among these, 18 were also diagnosed with syphilis, representing a co-infection occurrence of 38.3%. These results underscore a high occurrence of syphilis among HIV-positive patients. Faced with this reality, it is imperative to interrupt this transmission chain, reinforcing the importance of early diagnoses and the implementation of effective public policies in syphilis control.